2003
DOI: 10.1210/jc.2003-030424
|View full text |Cite
|
Sign up to set email alerts
|

Metformin or Antiandrogen in the Treatment of Hirsutism in Polycystic Ovary Syndrome

Abstract: Hirsutism is a common and distressing symptom frequently encountered in women with polycystic ovary syndrome (PCOS), who also show relative insulin resistance. The aim of this trial, in which hirsutism was the primary end point, was to compare the efficacy of the oral antihyperglycemic medication metformin with that of an established treatment, combined ethinyl estradiol and cyproterone acetate. Patients (n = 52) were randomized to receive either metformin (500 mg, three times daily) or Dianette (ethinyl estra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
99
0
3

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(107 citation statements)
references
References 31 publications
5
99
0
3
Order By: Relevance
“…Metformin significantly improved hirsutism in the current study, similar to both OCP groups, despite differential effects on androgen levels. One previous controlled study (2,25) reported the effects of metformin on hirsutism, demonstrating greater efficacy with metformin than with high-dose OCP. Potential mechanisms of action include improved IR and/or IGF-I activity, each of which are affected by metformin and involved in hair growth (25).…”
Section: Conclusion -In Women Withmentioning
confidence: 99%
“…Metformin significantly improved hirsutism in the current study, similar to both OCP groups, despite differential effects on androgen levels. One previous controlled study (2,25) reported the effects of metformin on hirsutism, demonstrating greater efficacy with metformin than with high-dose OCP. Potential mechanisms of action include improved IR and/or IGF-I activity, each of which are affected by metformin and involved in hair growth (25).…”
Section: Conclusion -In Women Withmentioning
confidence: 99%
“…Although the use of metformin (N,N 0 -dimethylbiguanide) is becoming accepted and widespread, it has been clinically used without a complete understanding of the mechanisms involved. Metformin reduces insulin resistance (Fedorcsak et al 2003, Harbone et al 2003, Lord et al 2003, affects ovarian steroidogenesis (La Marca et al 2002, Mansfield et al 2003, Tosca et al 2006a, and restores ovulation of anovulatory women with PCOS (Palomba et al 2004(Palomba et al , 2006. The treatment with metformin is also able to improve uterine vascularization in PCOS patients (Palomba et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…PCOS is a heterogeneous disorder, characterised by hyperandrogenism, chronic anovulation and infertility [2][3][4][5]. A significant proportion of PCOS women suffer from insulin resistance, which appears to play a role in the aetiology of PCOS, since amelioration of insulin resistance by lifestyle or pharmacological intervention has been shown to improve hyperandrogenism and fertility [6][7][8][9]. Furthermore, insulin resistance is proposed to be a major risk factor for the development of type 2 diabetes mellitus and subsequent cardiovascular disease [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%